Radiobiological evaluation of radiation cells survival based on linear quadratic and multi-target model - Raizulnasuha Binti Ab Rashid; Wan Nordiana Rahman (Journal of Medical Physics and Biophysics, 2020)
Radiobiological model such as linear quadratic is widely used in clinical radiotherapy to predict the biophysical response of the tumour cell to the radiation. This study investigates the radiation cell survival using Linear Quadratic and Multi-Target model and their radiobiological parameters. The experimental works were conducted in-vitro using HeLa cells that were irradiated using photon and electron beams of different energy. Cells irradiation were performed in full scatter condition and exposed to radiation doses ranges from 1 to 10 Gy. Clonogenic assay is used as an endpoint to obtain the cell survival curves which later be fitted with linear quadratic and multi-target model. The results demonstrate that Multi-target model produce the fitting curves that are closed to the experimental data compare to linear quadratic model especially at high doses. Parameter analysis from both models indicates more biological damage inflicted by high energy electron beam. Correlation between the experimental cell survival data and radiobiological model analysis suggesting that radiobiological model could be applied in analysing cells’ radiation survival and damage